Exergy Analysis of Coil-Spring Turbulators Inserted in the Horizontal Concentric Tubes - Eren, Haydar; Celik, Nevin; Kurtbas, Irfan; Yildiz, Seyba (Asme, 2010)
In this study, to obtain definitive information about the effects of spring-type turbulators located in the inner pipe of a concentric heat exchanger, the rates of exergy transfer Nusselt number (Nu(e)) and exergy loss (E*) were obtained. The results were parametrized by the Reynolds number (2500 < Re < 12,000), the outer diameter of the spring (D-s = 7.2 mm, 9.5 mm, 12 mm, and 13 mm), the number of the springs (n = 4, 5, and 6), and the incline angle of the spring (0 = 0 deg, 7 deg, and 10 deg). It is found that increasing those parameters results in a significant augmentation on exergy transfer comparative to the results of a smooth empty tube. A new term, exergy transfer Nusselt number, is derived in this paper. This term includes both irreversibility due to temperature gradient on the heat transfer surface and irreversibility due to pressure loss of the system. Hence, it is observed that optimum values of independent parameters for a constant surface temperature tube can be determined by this value. With regard to the maintained data, the irreversibility of heat transfer and pressure loss increases with increasing Re. However, at a certain value of Re, the increment rate of the irreversibility of heat transfer decreases, while the increment rate of the irreversibility of pressure loss increases. These results will contribute to adjust the system parameters such as the pump power and other independent parameters more easily. [DOI: 10.1115/1.4001926]
Keywords: heat transfer enhancement; heat exchangers; spring turbulator; exergy transfer